1988
DOI: 10.1016/0741-5214(88)90285-6
|View full text |Cite
|
Sign up to set email alerts
|

Routine revascularization with resection of infected femoral pseudoaneurysms from substance abuse

Abstract: Infected femoral artery pseudoaneurysms in narcotic addicts present challenging management options. Our policy of routine revascularization is based on the concern that a high rate of amputations must follow ligation and resection alone or with selective delayed revascularization. Fifteen of 16 patients with infected pseudoaneurysms of femoral arteries, treated with resection and bypass grafts, were observed from 1 to 44 months. Obturator bypass grafts were used in 10 patients, iliac-femoral grafts in three, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 9 publications
1
30
0
3
Order By: Relevance
“…Management policies that have been adopted include primary ligation and excision of the IFAP without revascularization [4,10], selective treatment with primary revascularization [8], and regular use of primary arterial reconstruction [9]. We present four cases of young addicts that were admitted to hospital with a ruptured IFAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management policies that have been adopted include primary ligation and excision of the IFAP without revascularization [4,10], selective treatment with primary revascularization [8], and regular use of primary arterial reconstruction [9]. We present four cases of young addicts that were admitted to hospital with a ruptured IFAP.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical management is difficult, and still controversial as to the necessity, selection, timing and method of revascularization, and without uniform recommendations [4,5,[8][9][10]. Management policies that have been adopted include primary ligation and excision of the IFAP without revascularization [4,10], selective treatment with primary revascularization [8], and regular use of primary arterial reconstruction [9].…”
Section: Introductionmentioning
confidence: 99%
“…When alternative routes of parenteral drug abuse are exhausted, the groin, 1,5,12,14,21 antecubital fossa, 1,21,24 and even the axilla 21 and neck are injected, so eventually complications will be brought to the vascular surgeon's attention. Although most infected false aneurysms (IFAs) attributed to repeated punctures involve the groin, 2,3,7-9, [13][14][15][16][17]19,21,22,[25][26][27] which is the easiest and preferred "anatomic site" used by the drug addict, 15 other locations such as the subclavian, 13 axillary, 28 brachial, 3,13,19,22,25 radial, 15,19 external iliac, 8 popliteal, 19,22 and even the carotid arteries have been reported as target sites of similar lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Should a pedal Doppler signal be present upon test clamping they suggest no further need for immediate arterial reconstruction. In contrast to Padberg et al, a study of 16 patients by Patel et al, reported on their use of aggressive revascularisation in such patients, with 15/16 patients undergoing immediate revascularisation upon vessel ligation and debridement, with only one late graft failure, whilst the remaining 14 patients had functional limbs with no claudication or rest pain [28]. Klonaris et al, documented their experience of utilising the internal iliac artery as a patch or conduit for arterial reconstruction in nine patients with infected false aneurysms secondary to IVDA [29], with the internal iliac artery being utilized as a patch in five patients and an interposition graft in four patients.…”
Section: Discussionmentioning
confidence: 87%